O gerador térmico como analisador de Propriedades térmicas a partir da Harmônica pura - Silva, Tássio Alessandro Borges da (2014)
This work presents a new method for determination of thermal properties of materials. As it makes use of two different materials at the time of measurement, it is a differential instrument. In the proposed method a thermal wave is generated at one end of the material and measured the temperature at the other end. Based on the relationship between the input and output waves is possible to obtain the thermal properties of the material. The equation of heat conduction in materials was deduced and simulated, to determine the temperature at any point of the materials. In the experimental setup two thermoelectric modules were used along with a PID control to generate a thermal wave and a module to maintain a constant temperature. The LabVIEW platform together with the cFP-2000 was used for data acquisition and control. Type T thermocouples were used as temperature sensors. The materials used in the experiments (ASTM A36 Steel, Nylon and Quartz) have their thermal properties provided by the manufacturers, these values were used as reference for validation. The developed instrument generates waves with amplitudes between 1 and 3 ° C and periods from 100 to 10000 seconds. To solve the problem of determining the temperature in the material, the analogy between thermal and electrical systems was applied, a technique called the Method of Simulation Network. The results were divided into three parts: The first introduces thermal sinusoid generated by the thermal generator and the second compares the theoretical values to the measured values of temperature between the two materials and the third displays the value of thermal conductivity measured by the instrument. The results were positive and indicate the feasibility of the method and instrument.